2013
DOI: 10.1017/s0144686x13000494
|View full text |Cite
|
Sign up to set email alerts
|

Place and wellbeing: shedding light on activity interventions for older men

Abstract: In the United Kingdom, one in five of the population is an older man, many of whom live alone. Loneliness and social isolation is a growing issue for many of these older men, one that has been associated with elevated blood pressure, poor physical health, increased mortality and mental ill-health, including depression, suicide and dementia. Lone dwelling and social isolation have tended to be viewed largely as issues affecting older women due to their greater life expectancy (LE), but the LE gap between men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 29 publications
4
82
1
1
Order By: Relevance
“…They have also engaged men in informal adult learning activities, provided health‐related information and referred men onto relevant services to promote their health and well‐being (Milligan et al . ). Men's Sheds offer a non‐threatening space for men to engage with other men (Milligan et al .…”
Section: Introductionmentioning
confidence: 97%
“…They have also engaged men in informal adult learning activities, provided health‐related information and referred men onto relevant services to promote their health and well‐being (Milligan et al . ). Men's Sheds offer a non‐threatening space for men to engage with other men (Milligan et al .…”
Section: Introductionmentioning
confidence: 97%
“…This study assessed Men's Shed members’ perceptions of the health and wellbeing benefits of shed activity in a large regional Queensland Men's Shed. The Men's Shed demographic profile in this study was similar to other Australian Men's Sheds . The membership consisted primarily of older men over the age of 70 years from all socio‐economic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent social cohesion and social capital is consistent with Men's Shed research elsewhere, where shedders have reported feeling equal with other shedders regardless of age or experience, and they feel socially connected and included . Participating in Men's Shed activities may take away fears of being lonely and socially disconnected during their retirement years when they may find it harder to make friends . Healthy social networks have found to diminish the adverse effects of retirement and social isolation, and many men need social contact as well as meaningful and challenging activity to maintain their sense of identify obtained through previous family and work roles…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations